Aplicación de la técnica didáctica de mapas mentales para mejorar el aprendizaje desarrollador en los educandos del 1er grado de secundaria en la I.E Divino Maestro - Bautista Vargas, Einer (2011)
The technique of teaching Maps Mentally emerges as a tool that allows decoding information and integrate the central image, radiating through associations of ideas through a nodal structure, improved learning developer in learners in secondary education. The overall objective of this research was to develop a pedagogical application of the technique of teaching mental maps in the improvement of learning developer in the first grade student's of secondary education in the field of Science Technology and Environment - natural science component Educational lnstitution of the "Divine Master"- Second Jerusalem. The technique of teaching Mind Maps, is theoretical in theory confirm the theories of radiant thinking, Theory of lnformation Transfer supported by Carney, underpinned by Freeman Transactional Theory and the Theory of the schemes and Heimlich Pittelman, and supported by hipotetizó these theories are as follows: The application of the technique of teaching mental maps, will significantly improve the learning developer in the first grade student's of secondary education in science technology and environment - natural science component of the Educational lnstitution "Divine Master " Second Jerusalem. The research design was quasi-experimental test with pre and post test. The sampte was comprised of 34 student's, selected by random sampling and random group of Grade 1. The implementation of the Technical Educational Mind Maps developed during the second quarter, leading to validate our research hypothesis, according to the statistics shows where the calculated Z (22.88) is higher than the tabulated z (1.64) which was accepted by The research hypothesis (H1), which means that the average scores of the capabilities of accumulation, information processing and radiant thinking of learners in the post-test (= 13.1) of the experimental group is higher than average Pre test(= 3.1) in the control group, ie that the implementation of the Technical Educational resources Maps Mentally significantly improved learning developer of the trainees of the first degree of El Diviñe Master, who were educated with the art teaching "Mind Maps"